Current problems of digital transformation in secondary education - V. L. Nazarov; D. V. Zherdev; A. V. Buinacheva (Образование и наука)
Introduction. The article continues the series of publications within the framework of the Russian Foundation for Basic Research (RFBR) project “Construction of a Fundamental Model for the Digital Transformation of the General Education System”.Aim. The aim of the study was to analyse the current state of development of digital educational services and the development of digital competencies by participants in the educational process.Methodology and research methods. The authors used the materials from a number of secondary monitoring studies; however, the current research is based on completely original material. The data obtained during the survey are published for the first time. The main method of collecting information is an electronic questionnaire based on Google forms. The survey respondents were participants in the educational process, predominantly permanently residing in the territory of the Sverdlovsk region (99% of respondents). The survey was conducted on a voluntary and completely anonymous basis.Results. The research results of the study suggest that the mastery of digital technologies by the participants in the educational process is insignificantly associated with the implementation of state strategic programmes in the field of digital transformation of education. Although the ongoing changes such as the development of digital infrastructure in the school, the accumulation of digital educational content, the development of specialised services, the increase in the level of digital literacy of teachers are necessary. However, within the framework of the existing education management system, the aforementioned changes do not provide significant motivation for the actual use of opportunities of digital infosphere in education. Accordingly, at the moment, the transformation process is taking place according to the worst (inertial) scenario.Scientific novelty. The article makes it possible to more accurately assess the situation in regional education in order to make current management decisions and provides reference points for longitudinal research aimed at achieving the main goal of the project as a potential basis for the educational strategy of the Russian Federation.